Changes in handwashing knowledge, attitudes, and practices among primary schoolchildren in Ulaanbaatar, Mongolia during the COVID-19 pandemic - Enkhbat, Munguntuul; Togoobaatar, Ganchimeg; Erdenee, Oyunchimeg; Takekuma, Katsumata Asako (Frontiers in Public Health, 2025)
IntroductionThe coronavirus disease 2019 (COVID-19) pandemic has highlighted the critical importance of handwashing as a preventive measure against the spread of SARS- CoV-2. This study aimed to assess changes in handwashing knowledge, attitudes, and practices (KAP) among primary schoolchildren in Ulaanbaatar, Mongolia, before and during the pandemic.MethodsA longitudinal study was conducted with 399 children aged 8–11 years, with data collected in December 2019 (pre-pandemic) and January 2021 (during the pandemic). A self-reported questionnaire was used to assess the children’s handwashing KAP, focusing on four critical moments for handwashing: after using the toilet, before eating, after touching visibly dirty or unhygienic things, and after coming home.ResultsThe results showed a significant increase in handwashing knowledge and attitudes during the pandemic, with the average knowledge score rising from 9.8 to 12.3 and the percentage of correct responses about critical handwashing moments increasing from 23.0 to 80.4%. Handwashing practices also improved, with an increased frequency of handwashing at critical moments, although practice before eating remained unchanged. Sociodemographic factors, such as sex, grade level, and parental education, were associated with handwashing behaviors. Girls were significantly more likely to engage in proper handwashing (AOR = 4.50, p < 0.01), while fourth-grade students showed higher odds of practicing proper handwashing than third-grade students (AOR = 5.27, p < 0.01). Fathers’ higher education and maternal self-employment were positively associated with proper handwashing, whereas fathers’ employment in public service was negatively associated. The overall KAP scores showed a significant increase during the pandemic, with a mean difference of 3.68 [95% CI = (4.06, 3.29), p < 0.01], indicating a notable improvement in handwashing behavior.DiscussionThese findings highlight the importance of health education and interventions in shaping children’s hygiene behaviors during global health crises, with lasting implications for public health strategies, particularly in resource-limited settings.